Optimization international airport capacity I Gusti Ngurah Rai Bali - I Gusti Putu Agung Giga Pasoepati Gusti; Wahyuni Putu Ika; Sinarta I Nengah (Master Program of Infrastructure and Environmental Engineering, Postgraduate Program, Warmadewa University, 2023)
This study discuss about optimization capacity on land new to I Gusti Airport International Ngurah Rai, Bali with review evaluation capacity moment this . Development Airport Ngurah Rai consists of of 2 ( two ) stages . Stage One consists of from development international terminal capacity 189,000 meters square . For Step second , development in the form of international terminal expansion to 265,891 meters. Development process stage I requires reclamation land area of 47 ( four twenty seven ) hectares , and when it's 35 ( three twenty five) hectares has reclaimed . Whereas the rest still in the licensing process and targeted done mid December 2018. Development process Phase II will need reclamation land area of 71 ( seven twenty one ) hectare . Based on plan development Stages I and II are the addition of an apron covering an area of 47.9 hectares so need conducted calculation optimization capacity airport Ngurah Rai with consider adequate condition of the apron and runway given by PT Angkasa Pura I considering that condition expansion more carry on will difficult because cost development consequence crisis global pandemic and vulnerable damage surroundings _ _ waters airport that can damage area . Study this aim for knowing amount movement the plane that will wearing a new apron To use serve movement aircraft in 2022. Analysis _ started with needs runway length in Maximum Take - off Weight (MTOW) for type aircraft largest operating _ in 2019 (Boeing 747 – 400), next analyze amount runway capacity and prediction year 2022 in operation mix (Take – off/Landing), and do analysis linear regression for estimate amount movement aircraft optimally for _ 2022. Continued _ with determine score rmonth , Rday , and the later Rhour multiplied with score results regression for get score Nmonth , Nday , and Nhour . Nhour value in year planning . Analysis result show evaluation condition existing runway 3000 m to runway needs with aircraft Boeing 747 – 400ER plan , then results correct to influence height from sea level (Fe) is 3323.4 m, while correct to influence temperature air (Ft) obtained 3620.4 m. amount movement aircraft in 2022 results _ analysis operating runway capacity arrival just is 18 operations per hour, for operation departure just is 44 operations per hour, whereas for operation mixture is 58 operations per hour. The result of parking stand requirements is obtained in class of aircraft 3 C as many as 34 parking stands and 4C as many as 45 parking stands. From result determination new apron capacity in 2022 with _ total dimensions 122130.4 m 2 . Next recommended for conducted analysis more carry on in the form of arrangement of parking stands on land reclamation stages I and II. for 2022 .